Pengaruh mekanisme corporate governance, audit tenure, dan kualitas audit terhadap nilai perusahaan - Sari, Kiki Evita Kenada; Widiatmoko, Jacobus; Indarti, Maria Goreti Kentris (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research needs to be done to review the value of a good company in the presence of several factors. These factors include good corporate governance: managerial ownership, independent commissioners, institutional ownership, audit tenure, audit committee, and audit quality. The purpose of this study is to examine the effect of corporate governance mechanisms on firm value, with firm size, leverage, and profitability as control variables. All manufacturing companies listed on the Indonesia Stock Exchange in 2019–2021 are the population of this study. The sample selection applied purposive sampling and obtained 393 data. Multiple linear regression analysis was used in this study. The results showed that there is an effect of managerial ownership, independent commissioners, and audit tenure on firm value. Meanwhile, institutional ownership, audit committee, and audit quality have no effect on firm value. Furthermore, all control variables affect firm value.